Connecting Women, Connecting Men: How Communities and Organizations Interact to Strengthen Adaptive Capacity and Food Security in the Face of Climate Change. (1st January 2016) - Cramer, Laura; Förch, Wiebke; Mutie, Ianetta; Thornton, Philip K.
Abstract: Given the different roles that women and men play in households and communities, strategies to improve food security and build adaptive capacity need to take gender differences into account. In many developing countries, local organizations have a role to play in it. However, the degree to which there is an overlap among the priorities of men, women, and organizations (including non-governmental bodies, local government offices, and other agencies working in the community) is not generally known, nor do we know whether organizations are strengthening the adaptive capacity of both men and women effectively and equally. Using gender-disaggregated data arising from community-level participatory research and organizational-level interviews from 15 sites across West Africa, East Africa, and South Asia, we conduct a cross-regional analysis of local organizational landscapes as they relate to livelihoods and food security. We find that in all regions, women tend to value local organizations more highly and thus appear to be less connected to external organizations than men. Additionally, women's perception of food security is broader than men's, going beyond a production focus. Most of the local organizations with food security as a stated objective focus on production, which can marginalize/alienate women. Given the effects that climate change is predicted to have on food security, development organizations should consider the differing priorities of men and women, and use a gendered perspective when building adaptive capacity to respond to climate change, and to maintain/improve food security. Such work can, perhaps, most effectively be implemented through existing community groups.